THE EXPRESSIONS OF PLANTING THE RICE IN THE PADDY PROCESSION IN MINANGKABAU SOCIETY AS ONE OF THE PILLARS OF CULTURE AND CHARACTER OF THE NATION - Eriza Nelfi; Iman Laili (International Conference on Languages and Arts, 2014)
This paper discusses the various Minangkabau expressions in the procession of planting the rice in Nagari Biaro Gadang, Kecamatan IV Angkat Candung, Kabupaten Agam, West Sumatra. The expressions are studied from ecolinguistics perspective. This article is funded by Dikti grant.  Based on ecology point of view, language is seen as a subsystem that has close relation with other subsystems. The change of subsystem causing changing of language used. One of the causes is the extinction of a number of phrases and lexicon in agricultural processing in Minangkabau society. The phenomena of the change is caused by the influence of globalization. The extinction of a number of the lexicons will also be followed by the extinction of a number of cultural assets and cultural values related to the cultural identity and village’s characters.  The aspect of cultural identity are essential in sustaining the character of national character.   Keywords: term of agricultural procession, Minangkabau, character of nation